2005
DOI: 10.1007/s10549-004-6454-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of metastases with a Mage-b DNA vaccine in a mouse breast tumor model: potential for breast cancer therapy

Abstract: Anti-tumor vaccines are a relatively non-toxic alternative to conventional chemotherapeutic strategies to control breast cancer. Immunization with tumor-associated antigens (TAAs) triggers anti-tumor cytotoxic T lymphocytes (CTL), which can limit tumor progression. Here we report on the development and effectiveness of a TAA-based DNA vaccine encoding Mage-b1/2, the mouse homologue of the human MAGE-B1/2. As model system, we used immune competent Balb/c mice with syngeneic non-metastatic (64pT) or metastatic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…In previous studies, we demonstrated that DNA vaccination with mouse Mage-b in metastatic mouse breast tumour models 4TO7cg and 4T1, highly expressing Mage-b, reduced the number of metastases significantly, although not completely (Sypniewska et al, 2005;Gravekamp, 2007;Gravekamp et al, 2008). In the study presented here, we further enhanced the efficacy of Mage-b vaccine through improved delivery of the vaccine using recombinant Listeria monocytogenes (LM).…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…In previous studies, we demonstrated that DNA vaccination with mouse Mage-b in metastatic mouse breast tumour models 4TO7cg and 4T1, highly expressing Mage-b, reduced the number of metastases significantly, although not completely (Sypniewska et al, 2005;Gravekamp, 2007;Gravekamp et al, 2008). In the study presented here, we further enhanced the efficacy of Mage-b vaccine through improved delivery of the vaccine using recombinant Listeria monocytogenes (LM).…”
mentioning
confidence: 65%
“…pcDNA3.1-Mage-b/V5 was developed in our laboratory (Sypniewska et al, 2005). Mouse GM-CSF plasmid (CMV1-GM-CSF) was kindly provided by Dr Stephen Johnston (the Center for Innovations in Medicine, the Biodesign Institute at Arizona State University) (Chambers and Johnston, 2003).…”
Section: Plasmids and Listeria Monocytogenesmentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse Mage-b DNA plasmid (pcDNA3.1-Mage-b/V5) has been described previously (Sypniewska et al, 2005). The mouse granulocyte macrophage-colony stimulating factor (GM-CSF) plasmid (CMV1-GM-CSF) was kindly provided by Dr Stephen Johnston (The Center for Innovations in Medicine, The Biodesign Institute at Arizona State University) (Chambers and Johnston, 2003).…”
Section: Plasmidsmentioning
confidence: 99%